The Forests of the Congo Basin: State of the Forest 2010 - Wasseige, C. de; Marcken, P. de; Bayol, N.; Hiol-Hiol F; Mayaux, P; Desclee, B; Nasi, Robert; Billand, A.; Defourny, Pierre; Eba'a Atyi, R. (European Union, 2012)
The 2010 State of the Forest report (SOF) benefited from financial support from the European Union, the United States, Germany, France and UNESCO. It represents the collaborative effort of over 100 individuals from a diversity of institutions and the forestry administrations of the Central African countries. The SOF process began with the selection and definition of indicators relevant to monitoring the state of forests in Central Africa. The indicators are structured around three thematic areas: (i) forest cover; (ii) management of production forests; and (iii) conservation and biodiversity. They are presented in a hierarchical structure at the regional, national and management unit (i.e. logging concessions and protected areas) levels. The indicators were vetted by a representative panel of stakeholders of forest management in Central Africa. The indicators are used to guide an annual data collection process carried out between April and August by national groups of four to ten individuals working within the forestry administrations. The data reported on in the 2010 SOF were primarily collected in 2009 and 2010. Results were validated in national workshops attended by government officials as well as representatives of environmental NGOs, the private sector and development projects. The data provided an important basis for the authors of the 11 chapters of the 2010 SOF, which were under the coordination of a scientific committee of international renown. A final workshop was held 29-30 March, 2011 in Douala to review a draft report. Following amendments based on comments from a wide audience of experts the final layout was completed.